Understanding the response heterogeneity of different cancer cell types toward anti-mitotic drugs I-Taxol - Tan, Adeline Hui Chen (2010)
Different types of cancer cells respond differently to anti-mitotic drug Taxol, resulting in its success and failure in its combat against cancer. Failure in the form of resistance of cancer cells to Taxol remains a huge obstacle for effective cancer treatment and for patients’ survival. In this study, we proposed that cellular proteins are the cause of the response heterogeneity. To identify the proteins of interest, cell lines HeLa cells and Taxol-resistant A549 cells were used for drug treatment, Bradford protein assay, SDS-PAGE and mass spectrometry. Western blotting was performed to ensure accuracy of the SDS-PAGE results. From the extensive MS analysis results, three proteins, Plectin, 78 kDa glucose-regulated protein precursor and Cullin-4B, were successfully shortlisted and further research studies are necessary to confirm that they are the proteins of interest.